Using a Product's Sustainability Space as a Design Exploration Tool. (7th January 2019) - Mattson, Christopher A.; Pack, Andrew T.; Lofthouse, Vicky; Bhamra, Tracy
Abstract : Sustainable design is often practiced and assessed through the consideration of three essential areas: economic sustainability, environmental sustainability, and social sustainability. For even the simplest of products, the complexities of these three areas and their tradeoffs cause decision-making transparency to be lost in most practical situations. The existing field of multiobjective optimization offers a natural framework to define and explore a given design space. In this paper, a method for defining a product's sustainability space (defined by economic, environmental, and social sustainability objectives) is outlined and used to explore the tradeoffs within the space, thus offering both the design team and the decision makers a means of better understanding the sustainability tradeoffs. This paper concludes that sustainable product development can indeed benefit from tradeoff characterization using multiobjective optimization techniques – even when using only basic models of sustainability. Interestingly, the unique characteristics of the three essential sustainable development areas lead to an alternative view of some traditional multiobjective optimization concepts, such as weak-Pareto optimality. The sustainable redesign of a machine to drill boreholes for water wells is presented as a practical example for method demonstration and discussion.